Intramuscular neridronate in patients with rheumatoid arthritis using corticosteroids: evaluation of treatment adherence in a randomized, open-label comparison with other bisphosphonates - Muratore, Maurizio; Quarta, Eugenio; Quarta, Laura (Acta Biomedica Atenei Parmensis, 2013)
Background and aims: Oral bisphosphonates have been used successfully in patients with rheumatoid arthritis (RA), but their use for the treatment of corticosteroid induced osteoporosis may be limited by poor compliance. Neridronate, an intramuscular and intravenous aminobisphosphonate approved for the treatment of osteogenesis imperfecta and Paget’s disease, is also effective in postmenopausal osteoporosis. The aim of this study was to compare the adherence of intramuscular neridronate versus oral alendronate or risedronate in patients with RA with corticosteroid-induced osteopenia. Methods: This randomised, open label, parallel-group, single centre study enrolled post-menopausal women (50–70 years), with RA and osteopenia (T-score >–2.5) who were receiving stable dose of methylprednisolone 5 mg or equivalent within the previous 3 months, and expected to continue therapy for at least 12 months. Patients were treated with intramuscular neridronate 25 mg administered once a month, or oral alendronate 70 mg or oral risedronate 35 mg both administered once-weekly, for 12 months. The main outcome measure was adherence to treatment over 1 year, assessed using the Morisky Medication Adherence Scale 4-item (MMAS-4; adherence defined as patients with MMAS-4 score ≥3). Results: Of 87 women (mean age 61.5 ± 9.2 years) enrolled, 30 were randomized to neridronate, 27 to alendronate and 30 to risedronate therapy. Adherence rates after 12 months were significantly higher with neridronate than with alendronate or risedronate (76.7% vs 47.8% and 48.0%; p